1960
DOI: 10.1083/jcb.7.2.335
|View full text |Cite
|
Sign up to set email alerts
|

An Electron Microscopic Investigation into the Effect of EDTA on Plant Cell Wall

Abstract: To study the effect of EDTA on cell wall structure and the reversal of this effect by uranyl ion, thin sections of pea root tips were examined in the electron microscope. EDTA is known to facilitate separation of the cells in root tips. When sections of fixed and embedded EDTA-treated roots are floated on a uranyl-acetate solution, a loose network is revealed that would seem to be cellulose. Incorporation of uranyl into the roots, if it occurs prior to fixation, brings about recementation of the cells. After s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1961
1961
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…In spite of the brevity of the enzyme treatment, this and the subsequent squashing are capable of weakening or perforating the cell wall sufficiently to allow it to pass antibody molecules. As reported earlier by others using much higher concentrations and longer exposures to another Ca" chelator, EDTA (19,21), inclusion of 5 mM EGTA in all processing steps appears to aid in the cell separation, and results in a higher proportion of intact, undistorted cells after the squashing. Permeabilized, isolated, stabilized plant cells obtained in this way react with affinity-purified antibodies to porcine brain tubulin to reveal microtubule arrays throughout all stages of the cell cycle .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In spite of the brevity of the enzyme treatment, this and the subsequent squashing are capable of weakening or perforating the cell wall sufficiently to allow it to pass antibody molecules. As reported earlier by others using much higher concentrations and longer exposures to another Ca" chelator, EDTA (19,21), inclusion of 5 mM EGTA in all processing steps appears to aid in the cell separation, and results in a higher proportion of intact, undistorted cells after the squashing. Permeabilized, isolated, stabilized plant cells obtained in this way react with affinity-purified antibodies to porcine brain tubulin to reveal microtubule arrays throughout all stages of the cell cycle .…”
Section: Discussionsupporting
confidence: 67%
“…Inclusion of EGTA in the fixative did not have a noticeable effect on microtubule preservation, but made possible the isolation of undamaged cells from roots incubated with any of the enzymes. This is presumably a result of partial dissolution, by means of Ca" chelation, of middle lamella Ca" pectates that "cement" adjacent cell walls together (19,21). Weakening of intercellular bonding was enhanced when EGTA was included in buffer rinses as well as in the fixative and enzyme solutions, yielding cells such as seen in Fig.…”
Section: Isolation Of Cellsmentioning
confidence: 99%
“…This short wash has not removed the stain completely, but the difference is most striking. The effect described here seems to be essentially the same as that observed by Klein & Ginzburg (1960), though with the techniques then available it was not possible to see the details of individual microfibrils in thin sections. These results show clearly that the staining reaction is physical in nature, and there is therefore no reason to doubt that the stained structures are the cellulose microfibrils of the wall.…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 60%
“…It has been reported that Versene has a disruptive effect upon the fine structure of plant cells (25), and the rat liver used for the present work responds in a similar way to this metalchelating agent. A m m o n i u m reineckate, on the other hand, improves the preservation of plant cells by reducing the extraction of phospholipid by formalin (26), probably through the formation of insoluble complexes with phospholipids (41).…”
Section: Discussionmentioning
confidence: 79%